The Role of Rhythmic Neural Synchronization in Rest and Task Conditions - Deco, Gustavo; Buehlmann, Andres; Masquelier, Timothée; Hugues, Etienne (Frontiers in Human Neuroscience, 2011)
Rhythmic neural synchronization is found throughout the brain during many different tasks and even at rest. Beyond their underlying mechanisms, the question of their role is still controversial. Modeling can bring insight on this difficult question. We review here our recent modeling results concerning this issue in different situations. During rest, we show how local rhythmic synchrony can induce a spatiotemporally organized spontaneous activity at the brain level. Then, we show how rhythmic synchrony decreases reaction time in attention and enhances the strength and speed of information transfer between different groups of neurons. Finally, we show that when rhythmic synchrony creates firing phases, the learning with STDP of repeatedly presented input patterns is greatly enhanced.